La responsabilidad penal de las personas jurídicas en las operaciones de M&A: ¿se puede eximir de responsabilidad penal a través de un adecuado due diligence de compliance penal? - Palao Vizcardo, Erick (2023)
This work focuses on analyzing how a legal entity can be criminally liable within the framework of an M&A operation, specifically in a merger or spinoff, due to an illicit act committed by the absorbed legal entity (target). However, the absorbing legal entity may be exempt from criminal liability if it conducts an adequate due diligence procedure before the M&A operation is finalized.Our regulations do not establish how appropriate due diligence should be carried out in the context of an M&A operation. Therefore, based on professional experience, we will propose a series of actions that the absorbing legal entity should take to demonstrate the completion of proper due diligence on issues of Criminal Compliance.